Upaya Peningkatan Kompetensi Kewirausahaan Kepala Sekolah Melalui Strategi Kepengawasan CINTA - Ekawati, Wahyu (Penerbit STKIP PGRI Bangkalan, 2022)
This study aims at improving the entrepreneurship competency of the school principal of through the managerial supervisory strategy of “CINTA” which stands for Coaching, Inquiry Appreciative, Negotiation, Tentukan Rencana Bisnis (Determining the business plan), and Aksi Nyata (the Real action). Through two cycles of the School Action Research (SAR), the implementation of the strategy at the private vocational high schools the researcher supervises, they are: SMKS 2 Pancasila Jember, SMKS Walisongo Rambipuji, and SMKS Al Imam Kalisat, Jember, the criteria of success have been achieved. The average score of school principals’ entrepreneurship increases from 40.28 to 93.33. One of the indicators is the school principals are able to create an innovation program of entrepreneurship development as school income generating unit which involves students as the subjects.